2004
DOI: 10.1002/lapl.200410129
|View full text |Cite
|
Sign up to set email alerts
|

Inverse problem of theory of the laser irradiation scattering in two-dimensional irregular integrated optical waveguide in the presence of statistic noise

Abstract: The linear inverse problem of the theory of the light scattering in two-dimensional integrated optical waveguide with statistical irregularities in presence of noise (non exact data) is investigated. The approximated correct solution of the inverse problem of the theory of waveguide scattering in hand is obtained for the natural physic and mathematics restrictions of imposed on a ``measured'' scattering pattern. The algorithm of restoring an autocovariance function of waveguide irregularities is based on a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In the general case, the irregularities can be either roughness of the interfaces of waveguide media or heterogeneities of the waveguide layer [1][2][3][4][5][6][7][8][9]. Rigorous solution of the inverse problem of the theory of waveguide scattering in an integrated optical waveguide is beyond the scope of this paper and will be given in one of our future publications (see, e.g., [13,14]). Indeed, the inverse problem of waveguide scattering is ill-posed [1-5, 10, 11].…”
Section: Analysis Of the Obtained Formula For The Green's Function Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general case, the irregularities can be either roughness of the interfaces of waveguide media or heterogeneities of the waveguide layer [1][2][3][4][5][6][7][8][9]. Rigorous solution of the inverse problem of the theory of waveguide scattering in an integrated optical waveguide is beyond the scope of this paper and will be given in one of our future publications (see, e.g., [13,14]). Indeed, the inverse problem of waveguide scattering is ill-posed [1-5, 10, 11].…”
Section: Analysis Of the Obtained Formula For The Green's Function Tmentioning
confidence: 99%
“…(14) and (3), we can explicitly write the desired Green's function G(x, y, z; x , y , z ) of the initial inhomogeneous three-dimensional wave equation (2):…”
Section: Derivation Of the Three-dimensional Waveguide Green's Functimentioning
confidence: 99%
“…Example include, in addition to nanotechnology, e.g., Refs. , laser scattering , seismology , climate science , molecular chemistry , analysis of infra‐red spectra of planetary surfaces , to name just a few.…”
Section: Inverse Approachmentioning
confidence: 99%
“…Although side-scattering properties of optical fibers and optical slab waveguides have been studied and corresponding experiments have been done, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] such studies of multilayer waveguide memories are seldom reported. We investigate this problem by building a simplified model.…”
Section: The Model Representationmentioning
confidence: 99%